Liquid/water level control of a single-tank system (hardware development) / Roshimee Jaffar @ Mustapha - Jaffar @ Mustapha, Roshimee (1996)
The competitive pressures in batch processing plant productions and difficulties in planning and control all call for improved design of batch plants thus provide an incentive for application of computer-aided methods. The selected plant is a Liquid/Water Level Control of Single Tank System. In analyzing a system involving fluid flow, it is necessary to divide flow regimes into laminar and turbulent flow. Industrial processes often involve flow of liquids through connecting pipes and tanks, and it is often a turbulent flow. This project is a pilot plant of a batch process and looks up in controlling the water level as its variable. The system is designed for liquids (particularly water) at atmospheric pressure in non-hazardous area and can be applied for industrial process, house used and Jabatan Park dan Saliran (JPS). This pilot plant gives the closer looks and the understanding about the real process in batch process plant.